2015
DOI: 10.1038/nature14228
|View full text |Cite
|
Sign up to set email alerts
|

A gp130–Src–YAP module links inflammation to epithelial regeneration

Abstract: Summary Inflammation promotes regeneration of injured tissues through poorly understood mechanisms, some of which involve interleukin (IL)-6 family members whose expression is elevated in many diseases, including inflammatory bowel diseases (IBD) and colorectal cancer (CRC). We show that gp130, a co-receptor for IL-6 cytokines, triggers activation of YAP and Notch, transcriptional regulators that control tissue growth and regeneration, independently of the classic gp130 effector STAT3. Through YAP and Notch, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
545
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 556 publications
(580 citation statements)
references
References 58 publications
31
545
2
2
Order By: Relevance
“…The Rho family GTPases Rac and Rho are thought to contribute to YAP activation by oncogenic mutants of GNAQ in a manner dependent on actin polymerization (46). Phosphorylation of YAP at Tyr 357 by c-Src increases the stability of the protein, and this action of c-Src has been implicated in the promotion of IEC proliferation (47). Such tyrosine phosphorylation by c-Src of YAP was demonstrated to occur under mucosal injury of the intestine (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rho family GTPases Rac and Rho are thought to contribute to YAP activation by oncogenic mutants of GNAQ in a manner dependent on actin polymerization (46). Phosphorylation of YAP at Tyr 357 by c-Src increases the stability of the protein, and this action of c-Src has been implicated in the promotion of IEC proliferation (47). Such tyrosine phosphorylation by c-Src of YAP was demonstrated to occur under mucosal injury of the intestine (47).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of YAP at Tyr 357 by c-Src increases the stability of the protein, and this action of c-Src has been implicated in the promotion of IEC proliferation (47). Such tyrosine phosphorylation by c-Src of YAP was demonstrated to occur under mucosal injury of the intestine (47). In contrast, we failed to detect the phosphorylation of YAP at Tyr 357 in crypts isolated from the small intestine of either control or Csk CKO mice under the steady-state condition (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the intracellular signaling activated by the proinflammatory cytokines, growth factors, or by the intrinsic proliferative signals may interact and co-operate to efficiently conduct the repair process. Accordingly, a recent study has shown that gp130, a co-receptor of IL-6, may activate both YAP and Notch and contribute to the tissue repair of the colitic mucosa [77].…”
Section: Mechanism Of Epithelial Repair In Ibdmentioning
confidence: 99%
“…SFK activity (Src and Yes) has been shown recently to favor YAP nuclear translocation. 39 It would be important to determine how, upon cancer-associated dismantling of cell-cell junction, PrP c , which interacts with YAP, could modulate its activation as well. In order to determine how the mechanisms that involve PrP c in cancer process and EMT are integrated, the analysis of the respective proportions and subcellular localizations of PrP c , Src, b-catenin, TCF, g-catenin, YAP and TAZ in a large-scale study of human tumors would be of great interest.…”
Section: Prp C Interaction With Junctional and Nuclear Partners: A Romentioning
confidence: 99%